Measurement of Student Satisfaction with the Application of Communicative Language Teaching Method in Indonesian Higher Education - mas'ud muhammadiah; Andi Hamsiah; Miftachul Amri; Dian Heriani; Defi Irwansyah (International Journal of Language and Ubiquitous Learning, 2024)
Background. Higher education in Indonesia increasingly emphasizes the importance of developing effective and innovative language skills to prepare students to face global challenges in the future. In language learning, the Communicative Language Teaching method is a popular approach because it emphasizes authentic communicative use of language. Purpose. This research aims to measure the level of student satisfaction with the application of the Communicative Language Teaching method in Indonesian higher education. Apart from that, it also aims to provide better insight into the effectiveness of its use in higher education in Indonesia. Method. The research method used in this research is a quantitative method. Data collection was carried out through questionnaires distributed to students from several universities in Indonesia that apply the Communicative Language Teaching method. The questionnaire is designed to assess certain aspects of the student's learning experience. Results. The research results showed that the majority of students responded positively to the application of the Communicative Language Teaching method through the questionnaires given. The results of data analysis also stated that there was a high increase in student satisfaction in the learning experience using the Communicative Language Teaching method. This method also helps improve their ability to communicate in the target language. Conclusion. The conclusion of this research shows that the Communicative Language Teaching method has a positive influence on students at Indonesian universities. Using this method not only improves their language skills but also enriches their learning experience through active social interaction. The implication of this research is that there needs to be more emphasis on the development and implementation of communication-oriented learning methods in the higher education curriculum in Indonesia.